Transcatheter Myocardial Needle Chemoablation During Real-Time Magnetic Resonance Imaging: A New Approach to Ablation Therapy for Rhythm Disorders. (April 2016) - Rogers, Toby; Mahapatra, Srijoy; Kim, Steven; Eckhaus, Michael A.; Schenke, William H.; Mazal, Jonathan R.; Campbell-Washburn, Adrienne; Sonmez, Merdim; Faranesh, Anthony Z.; Ratnayaka, Kanishka; Lederman, Robert J.
Abstract : Background—: Radiofrequency ablation for ventricular arrhythmias is limited by inability to visualize tissue destruction, by reversible conduction block resulting from edema surrounding lesions, and by insufficient lesion depth. We hypothesized that transcatheter needle injection of caustic agents doped with gadolinium contrast under real-time magnetic resonance imaging (MRI) could achieve deep, targeted, and irreversible myocardial ablation, which would be immediately visible. Methods and Results—: Under real-time MRI guidance, ethanol or acetic acid was injected into the myocardium of 8 swine using MRI-conspicuous needle catheters. Chemoablation lesions had identical geometry by in vivo and ex vivo MRI and histopathology, both immediately and after 12 (7–17) days. Ethanol caused stellate lesions with patchy areas of normal myocardium, whereas acetic acid caused homogeneous circumscribed lesions of irreversible necrosis. Ischemic cardiomyopathy was created in 10 additional swine by subselective transcoronary ethanol administration into noncontiguous territories. After 12 (8–15) days, real-time MRI–guided chemoablation—with 2 to 5 injections to create a linear lesion—successfully eliminated the isthmus and local abnormal voltage activities. Conclusions—: Real-time MRI–guided chemoablation with acetic acid enabled the intended arrhythmic substrate, whether deep or superficial, to be visualized immediately and ablated irreversibly. In an animal model of ischemic cardiomyopathy, obliteration of a conductive isthmus both anatomically and functionally and abolition of local abnormal voltage activities in areas of heterogeneous scar were feasible. This represents the first report of MRI-guided myocardial chemoablation, an approach that could improve the efficacy of arrhythmic substrate ablation in the thick ventricular myocardium. Abstract : Supplemental Digital Content is available in the text.